Not All Emissions Are Created Equal: Multidimensionality in Nations’ Greenhouse Gas Emissions and the Affluence/Emissions Nexus - Xiaorui Huang (Socius, 2024)
This study proposes a multidimensional emissions profile (MEP) framework, aiming to analyze how a broad social force systematically and heterogeneously affects four emission components of nations: (1) emissions generated by domestic-oriented supply chain activities, (2) emissions embodied in imports, (3) emissions embodied in exports, and (4) direct emissions of end-user activities. I implement a multiregional input-output approach to operationalize these emission components. Using the MEP framework and dynamic fixed-effects models with the seemingly unrelated regression estimator, I find these four emission components are heterogeneously related to national affluence in high-income nations. As these nations become even wealthier, affluence is gradually decoupled from emissions generated by domestic-oriented supply chain activities and direct end-user emissions, yet it remains strongly coupled with the other two emission components in distinct ways. The findings demonstrate the MEP framework’s utility and contribute a multidimensional perspective to the debate on the economic development–climate change relationship.